2020
DOI: 10.3389/fmicb.2020.601054
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Alters the Soil Microbial Diversity and Community to Facilitate Nitrogen Assimilation: A Potential Mechanism for Increasing Proso Millet Grain Yield

Abstract: Intercropping of cereals and legumes has been used in modern agricultural systems, and the soil microorganisms associated with legumes play a vital role in organic matter decomposition and nitrogen (N) fixation. This study investigated the effect of intercropping on the rhizosphere soil microbial composition and structure and how this interaction affects N absorption and utilization by plants to improve crop productivity. Experiments were conducted to analyze the rhizosphere soil microbial diversity and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 76 publications
5
38
1
Order By: Relevance
“…Other studies have reported a similar trend where cereal-legume intercropping increases overall diversity of soil microorganisms. Such observations have been made in wheat-soybean intercropping (Bargaz et al 2017), maize/wheat-faba bean intercropping (Wang et al 2020) and millet-mung bean intercropping (Dang et al 2020). While intercropping with annual legumes may cause a temporary shift in the soil microbial profiles, the impact of perennial crops and intercrops, such as Desmodium spp., on soil microbial diversity is likely to be stronger and more resilient.…”
Section: Diversity Of Cropping Systems Links To Diversity In Soil Microbiomementioning
confidence: 93%
“…Other studies have reported a similar trend where cereal-legume intercropping increases overall diversity of soil microorganisms. Such observations have been made in wheat-soybean intercropping (Bargaz et al 2017), maize/wheat-faba bean intercropping (Wang et al 2020) and millet-mung bean intercropping (Dang et al 2020). While intercropping with annual legumes may cause a temporary shift in the soil microbial profiles, the impact of perennial crops and intercrops, such as Desmodium spp., on soil microbial diversity is likely to be stronger and more resilient.…”
Section: Diversity Of Cropping Systems Links To Diversity In Soil Microbiomementioning
confidence: 93%
“…Particularly, in salinized soils, monoculture farming faces a double combination of excess salinity and continuous cropping obstacles. To overcome these problems, intercropping can be considered a novel approach to increase the efficiency of resource utilization, management of soil-borne diseases, and tolerance of farmland ecosystem stress ( Li Q. et al, 2016 ; Guo et al, 2018 ; Dang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also therefore likely that the Pseudomonas and Xanthomonas species found in the Proteobacteria phylum in this study were the beneficial rather than pathogenic species, given the greater abundance of mutualistic microbes such as Flavobacteriales, Sphingobacteriales, Bascillales, Phycisphaerae, Rhizobiales, and Sphingomonadales found in this same study. Dang et al (2020) found similar changes in some bacterial taxa, especially Proteobacteria, in a mung bean-millet intercropping system. Even with a tomato/potato-onion intercropping devoid of legumes, there was an alteration in soil microbial communities (Li et al, 2020), suggesting that changes in rhizosphere microflora is not unique to legume-cereal systems, but more likely an outcome of the composition of root exudates released by the intercropped partners.…”
Section: Response Of Rhizosphere Microbial Community To Cropping Systemsmentioning
confidence: 55%
“…Although rhizosphere microbial composition used to be studied by culturing the bacteria for single species interactions, now however, root-microbe interactions and the composition of root-associated microbial community have become easier to assess, with the development of next generation sequencing (Mendes et al, 2013;Hacquard et al, 2015). Furthermore, while several studies have been conducted on intercropping (Wahua, 1984;Li and Wu, 2018;Dang et al, 2020;Li et al, 2020), to our knowledge little is known about intra-hole cropping of legumes and cereals. We hypothesized that intra-hole cropping of cowpea-maize, and cowpea-sorghum would influence soil P-enzyme activity, mineral nutrient accumulation and microbial communities based on the partners used in the intra-hole cropping system.…”
Section: Introductionmentioning
confidence: 99%